2018
DOI: 10.1016/j.ajme.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Safe injection procedures, injection practices, and needlestick injuries among health care workers in operating rooms

Abstract: Background: Of the estimated 384,000 needle-stick injuries occurring in hospitals each year, 23% occur in surgical settings. This study was conducted to assess safe injection procedures, injection practices, and circumstances contributing to needlestick and sharps injures (NSSIs) in operating rooms. Methods: A descriptive cross sectional approach was adopted. Modified observational checklists based on World Health Organization (WHO) definitions were used in operating rooms (n = 34) and interview questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
0
12
2
1
Order By: Relevance
“…A study conducted in Egypt (2017) showed that 41.9% of HCWs cleaned their hands with soap and water or alcohol-based hands rub and 58.1% of HCWs were not wearing gloves during IV injection. (29) The study revealed that the vial was disinfected with alcohol in 67.5% of the observations. A study conducted in USA (1994) showed that the vials were disinfected with alcohol and povidoneiodine in 95% of the observations.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Egypt (2017) showed that 41.9% of HCWs cleaned their hands with soap and water or alcohol-based hands rub and 58.1% of HCWs were not wearing gloves during IV injection. (29) The study revealed that the vial was disinfected with alcohol in 67.5% of the observations. A study conducted in USA (1994) showed that the vials were disinfected with alcohol and povidoneiodine in 95% of the observations.…”
Section: Discussionmentioning
confidence: 99%
“…Respecto a las prácticas documentadas en la literatura, el personal utiliza insumos provenientes de paquetes estériles, cerrados y desechables, y su preparación se lleva a cabo en espacios limpios. Son las acciones subsecuentes como el reúso de los dispositivos, la contaminación de los viales y soluciones y los lapsus en la técnica aséptica, los que afectan la seguridad del procedimiento y contradicen los estudios que arman que el personal posee los conocimiento adecuados (32,34,35,(38)(39)(40)42,45,(48)(49)(50).…”
Section: Discussionunclassified
“…Surgical centers are the environment of 23% of sharps injuries. The factors associated with sharps injuries include all previously mentioned unsafe measures, and factors such as absence of accident reports and lack of post-exposure prophylactic treatment can be highlighted (28) . It is worth noting that the context around occupational incidents does not always involve emergency situations (29) , which shows the possibility of planning preventive actions in relation to these events.…”
Section: Discussionmentioning
confidence: 99%